2016
DOI: 10.1021/acsami.6b02790
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Docetaxel by Use of Transferrin/Poly(allylamine hydrochloride)-functionalized Graphene Oxide Nanocarrier

Abstract: The exceptional chemical and physical properties of graphene oxide (GO) make it an attractive nanomaterial for biomedical applications, particularly in drug delivery. In this work we synthesized a novel, GO-based nanocarrier for the delivery of docetaxel (DTX), a potent hydrophobic chemotherapy drug. The GO was functionalized with transferrin (Tf)-poly(allylamine hydrochloride) (PAH), which provided targeted and specific accumulation to extracellular Tf receptors and stabilized GO in physiological solutions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 62 publications
(118 reference statements)
0
43
0
Order By: Relevance
“…The targeting efficiency was evaluated against MCF‐7 breast tumor cells. In contrast to free DTX that showed low cytotoxicity at a high DTX concentration, improved cytotoxicity of Tf‐modified DTX nanomedicine was observed as a result of the targeting effect and enhanced stability in cell medium . As aforementioned, drug delivery mediated by positive targeting initially relies on the passive targeting, which suggests that the positive and passive drug delivery mechanisms are interrelated.…”
Section: Positive Targetingmentioning
confidence: 95%
See 1 more Smart Citation
“…The targeting efficiency was evaluated against MCF‐7 breast tumor cells. In contrast to free DTX that showed low cytotoxicity at a high DTX concentration, improved cytotoxicity of Tf‐modified DTX nanomedicine was observed as a result of the targeting effect and enhanced stability in cell medium . As aforementioned, drug delivery mediated by positive targeting initially relies on the passive targeting, which suggests that the positive and passive drug delivery mechanisms are interrelated.…”
Section: Positive Targetingmentioning
confidence: 95%
“…In contrast to free DTX that showed low cytotoxicity at a high DTX concentration, improved cytotoxicity of Tf-modified DTX nanomedicine was observed as a result of the targeting effect and enhanced stability in cell medium. [40] As aforementioned, drug delivery mediated by positive targeting initially relies on the passive targeting, [22] which suggests that the positive and passive drug delivery mechanisms are interrelated. Adopting Tf as the positive targeting group (Figure 3), Singh et al found both the passive targeting and positive targeting exhibited dose-dependent therapeutic distinction.…”
Section: Transferrinmentioning
confidence: 99%
“…This would allow for reducing the drugs dosage, their concentrations on sites that are not of interest, and the side effects associated with chemotherapy and hormonal therapy [15,16]. In this regard, carbon nanomaterials with potential uses for the administration of drugs against cancer and breast cancer are being analyzed [17,22,23,[29][30][31]; they are considered as advantageous systems to control drug release in the organism and increase the efficiency of treatments and reduce their toxicity [17,32,33]. However, carbon nanomaterials have some disadvantages including their lack of solubility and low reproduction rate through their chemical functionalization and structural characterization.…”
Section: Drug Releasementioning
confidence: 99%
“…Many properties of carbon nanomaterials, such as size, shape, surface structure and charge, chemical composition, aggregation and/or agglomeration, and solubility, can greatly influence their interactions with biomolecules and cells. For example, carbon nanomaterials have been employed to produce exceptional images of tumor sites [20,21], impressive potential as high-efficiency delivery transporters for drugs and/or biomolecules into cells [20,22,23]. Therefore, the main emphasis of this article focuses on the discussion of carbon nanomaterials and their current applications in the identification, diagnosis, and treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The unique properties of graphene derivatives have made them attractive nanomaterials in drug delivery and biomaging . Among graphene derivatives, graphene quantum dots (GQDs) have minimum toxicity owing to their ultra‐small size (<10 nm) and oxygen functional groups in their structure .…”
Section: Introductionmentioning
confidence: 99%